Adsorption Races of Binary Colloids with Different Softness at the Air/Water Interface of Sessile Droplets. Issue 28 (10th August 2022) - Minato, Haruka; Sasaki, Yuma; Honda, Kenshiro; Watanabe, Takumi; Suzuki, Daisuke
Abstract: Although methods to suppress macroscopic nonuniform structures, e.g., due to the coffee‐ring effect, have been established, the formation of specific patterns during the evaporation of water from sessile droplets that contain colloidal particles remains challenging. In this study, it is discovered that the surface modification of colloidal particles by soft hydrogels provides a means to control the adsorption kinetics on the air/water interface. Especially binary mixtures of such core/shell colloids exhibit unique adsorption behavior that manifests in adsorption races to the interface, resulting in the formation of patterns of binary colloidal particles as well as in a suppression of the coffee‐ring effect. These results can be expected to be beneficial for applications such as inkjet coating, where the required micro‐patterns are controlled via the evaporation of solvents. Abstract : The surface modification of colloidal particles by soft hydrogels provides a means to control the adsorption behavior at the air/water interface of sessile droplets. Especially binary mixtures of such particles exhibit unique adsorption behavior that manifests in adsorption races to the interface, resulting in the micropattern formation of binary particles as well as in a suppression of the coffee‐ring effect.